Oral Health Status of Illicit Drug Users in a Health District in South Africa - Mukhari-Baloyi, Ntsakisi; Bhayat, Ahmed; Madiba, Thomas K.; Nkambule, Ntombizodwa R. (European Journal of Dentistry, 2022)
Objectives The prevalence of illicit drug use and its associated oral health complications have been increasing in South Africa (SA). There has been a paucity of studies to determine the oral health status among illicit drug users in SA. This study aimed to determine the oral health knowledge, practices, and status of illicit drug users at rehabilitation centers in a district in SA.Materials and Methods This was a cross-sectional study conducted at four rehabilitation centers in Pretoria, SA. Data were collected using a validated self-administered questionnaire and an oral examination. The questionnaire consisted of three parts: demographics, oral health knowledge, and oral health practices. The oral examination was conducted by a calibrated researcher and included caries, periodontal status, dental erosion, trauma, and soft tissue lesions.Statistical Analysis The data were analyzed using the Statistical Package for Social Sciences (SPSS) software.Results The mean age was 25.5 (±7.49) years with 91% being male. The majority (84%) of patients were Black, and almost all (87%) had never received oral health education; 55% were not aware that illicit drugs could have an impact on the oral health status and 40% had never had a prior dental consultation. The caries prevalence was 68% with a mean decayed, missing and filled teeth (DMFT) score of 5.3 (±6.18). More than half (58%) required periodontal treatment and there were minimal soft and hard tissue lesions diagnosed. Those who perceived their teeth to be in a poor condition had a significantly higher Decayed, Missing and Filled Teeth (DMFT) score compared with those who perceived their oral health to be good. Just under half (41.9%) of the participants did not need any periodontal intervention, with the other half presenting with plaque retention or calculus and thus needed oral hygiene intervention inclusive of scaling and polishing. There was minimal evidence of pathological oral lesions with only 1.5% presenting with necrotizing periodontal disease (NPD). Overall, there was generalized poor oral hygieneConclusion Many of the participants had poor oral hygiene knowledge and practices and a relatively high prevalence of caries. It is imperative that oral health promotion and education is incorporated into the medical interventions provided at rehabilitation centers.
Keywords: recreational drugs; oral health; epidemiology; illicit drugs-adverse effects